Experimental Pulmonary Hypertension Is Associated With Neuroinflammation in the Spinal Cord - Vaillancourt, Mylene; Chia, Pamela; Medzikovic, Lejla; Cao, Nancy; Ruffenach, Gregoire; Younessi, David; Umar, Soban (Frontiers in Physiology, 2019)
Rationale: Pulmonary hypertension (PH) is a rare but fatal disease characterized by elevated pulmonary pressures and vascular remodeling, leading to right ventricular failure and death. Recently, neuroinflammation has been suggested to be involved in the sympathetic activation in experimental PH. Whether PH is associated with neuroinflammation in the spinal cord has never been investigated. Methods/Results: PH was well-established in adult male Wistar rats 3-weeks after pulmonary endothelial toxin Monocrotaline (MCT) injection. Using the thoracic segments of the spinal cord, we found a 5-fold increase for the glial fibrillary acidic protein (GFAP) in PH rats compared to controls (p<0.05). To further determine the region of the spinal cord where GFAP was expressed, we performed immunofluorescence and found a 3 to 3.5-fold increase of GFAP marker in the grey matter, and a 2 to 3-fold increase in the white matter in the spinal cord of PH rats compared to controls. This increase was due to PH (MCT vs. Control; p<0.01), and there was no difference between the dorsal versus ventral region. PH rats also had an increase in the pro-inflammatory marker chemokine (C-C motif) ligand 3 (CCL3) protein expression (~ 3-fold) and (2.8 to 4-fold, p<0.01) in the white matter. Finally, angiogenesis was increased in PH rat spinal cords assessed by the adhesion molecule CD31 expression (1.5 to 2.3-fold, p<0.01). Conclusion: We report for the first time evidence for neuroinflammation in the thoracic spinal cord of pulmonary hypertensive rats. The impact of spinal cord inflammation on cardiopulmonary function in PH remains elusive.